Implementasi Kurikulum Merdeka dalam Mewujudkan Pendidikan yang Berkualitas di SDN 154 Tulekko Kebupaten Bulukumba - Muh. Hapis; Syarifah Aeni Rahman; Rubianto Rubianto (Departement of Mathematics Education, 2024)
The main problem in this research is what is the level of implementation of the independent curriculum in realizing quality education at SDN 154 Tulekko Regency. Bulukumba. This research aims to determine the implementation of the independent curriculum in realizing quality education at SDN 154 Tulekko Regency. Bulukumba. This type of research is descriptive qualitative research, namely the data collected is in the form of words, images, not numbers. The samples used were the principal, homeroom teacher of classes I and IV and 2 students of classes I and IV. The instruments used to collect data were observation, interviews and documentation. Based on the results of research conducted by researchers regarding the implementation of the independent curriculum in realizing quality education at SDN 154 Tulekkon, Bulukumba Regency. The results obtained from the school community, namely the principal, homeroom teacher and representatives of students in grades 1 and 4, were used as informants in this research. Implementation of the Independent Curriculum at SDN 154 Tulekko, Bulukumba Regency. The implementation system is gradual, so the first year is grades 1 and 4. The second year follows grades 2 and 5. The implementation of the independent curriculum at SDN 154 Tulekko, Bulukumba Regency, which needs to be prepared, of course there is cooperation or collaboration between the school, be it the principal, teachers or students. . In this case, IKM program planning. Factors that become obstacles or obstacles in implementing independent learning at SDN 154 Tulekko, Bulukumba Regency are limited resources and difficulties in formative assessment.